QUARTER-LIFE CRISIS PHENOMENON (VIEWS AND SOLUTION ACCORDING TO ISLAMIC PSYCHOLOGY) - Hidayat, Ajat; Safni, Pela; Padila, Cisia; Afnibar, Afnibar; Ulfatmi, Ulfatmi (Al-Ittihad: Jurnal Pemikiran dan Hukum Islam, 2024)
Quarter-life crisis is a feeling of doubt, fear, and decision about facing the future related to personal matters or social relations with other people, including careers, friendships, family, and even love life that is experienced by the age of 20 years. A Quarter-life crisis is synonymous with fear, anxiety, anxiety, doubt, and decision about facing the future. This study aims to find out how the quarter-life crisis is in the view of Islamic psychology and its solutions. This research was conducted using a qualitative method with a literature study approach. In this study, the series of activities are concerned with collecting library data, reading and taking notes, then processing the appropriate and necessary information to answer the formulation of the problem to be solved. As for the results of this study in Islam, fear is called khauf. Khauf and fear because this quarter life crisis is different because khauf is meant only for Allah. The solutions to overcome the quarter-life crisis are: Increasing spiritual intelligence, increasing religiosity (intelligence and obedience to Allah), Prayer Worship, reading the Alquran regularly understanding its meaning, and being kind to Allah.